2023
DOI: 10.1161/strokeaha.123.044267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time to Thrombolysis on Clinical Outcomes in Patients With Acute Ischemic Stroke Treated With Tenecteplase Compared to Alteplase: Analysis From the AcT Randomized Controlled Trial

Nishita Singh,
Mohammed A. Almekhlafi,
Fouzi Bala
et al.

Abstract: BACKGROUND: The AcT (Alteplase Compared to Tenecteplase) randomized controlled trial showed that tenecteplase is noninferior to alteplase in treating patients with acute ischemic stroke within 4.5 hours of symptom onset. The effect of time to treatment on clinical outcomes with alteplase is well known; however, the nature of this relationship is yet to be described with tenecteplase. We assessed whether the association of time to thrombolysis treatment with clinical outcomes in patients with acute … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In patients undergoing thrombectomy included in the Intravenous Tenecteplase Compared With Alteplase for Acute Ischemic Stroke in Canada (AcT) trial, no significant difference in outcomes between patients allocated to IVT with alteplase vs tenecteplase was observed. Although the influence of time on clinical outcomes appears similar in patients treated with alteplase and in patients treated with tenecteplase, the potentially higher efficacy of tenecteplase in patients with large-vessel occlusion stroke undergoing thrombectomy observed in the Tenecteplase versus Alteplase Before Endovascular Therapy for Ischemic Stroke (EXTEND-IA TNK) trial may lead to different magnitudes and cutoffs in the observed associations. Ongoing trials, including the Randomization to Endovascular Treatment Alone or Preceded by Systemic Thrombolysis With Tenecteplase in Ischemic Stroke (DIRECT-TNK) trial (NCT05199194), aim to answer this specific question.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing thrombectomy included in the Intravenous Tenecteplase Compared With Alteplase for Acute Ischemic Stroke in Canada (AcT) trial, no significant difference in outcomes between patients allocated to IVT with alteplase vs tenecteplase was observed. Although the influence of time on clinical outcomes appears similar in patients treated with alteplase and in patients treated with tenecteplase, the potentially higher efficacy of tenecteplase in patients with large-vessel occlusion stroke undergoing thrombectomy observed in the Tenecteplase versus Alteplase Before Endovascular Therapy for Ischemic Stroke (EXTEND-IA TNK) trial may lead to different magnitudes and cutoffs in the observed associations. Ongoing trials, including the Randomization to Endovascular Treatment Alone or Preceded by Systemic Thrombolysis With Tenecteplase in Ischemic Stroke (DIRECT-TNK) trial (NCT05199194), aim to answer this specific question.…”
Section: Discussionmentioning
confidence: 99%